Impact of institutionalization in family-owned companies and elements of intellectual capital on competitive power: A research on hospitality business - Nuray Turkoglu; Ali Dalgic (The International Journal of Management Science and Information Technology (IJMSIT), 2017)
In this study, it was aimed to examine the impact of institutionalization in family-owned hospitality businesses and elements of intellectual capital on competitive power. Data was gathered with survey technique and analyzed through statistical databases for social sciences. According to the results of analysis, institutionalization has been explained with three factors, intellectual capital has been analyzed with two factors. While the elements of institutionalization has been defined as professionalization with organizational culture, and accountability and formalization,the dimensions of intellectual capital have been defined as customer capital, human capital and structural capital. In the study, no meaningful interaction has been found between formalization in family-owned businesses and human capital, and it was determined that competitive power was positively affected by organizational culture, customer capital and structural capital. Besides, it was seen that there was a meaningful but even negative impact of accountability on competitive power.
Keywords: 650; Institutionalization; Intellectual Capital; Competitive Power; Family-owned Businesses; Hospitality Businesses